И-сторија за еден крај. Кон Dejan Jović, Jugoslavija - država koja je odumrla: Rrëfimi për historinë e një visi. Për Dejan Jović, Jugoslavija - država koja je odumrla - Stefoska, Irena; Ahmeti, Lindita (Identities: Journal for Politics, Gender and Culture, 2003)
Author(s): Irena Stefoska | Ирена Стефоска Title (Macedonian): И-сторија за еден крај. Кон Dejan Jović, Jugoslavija - država koja je odumrla Title (Albanian): Rrëfimi për historinë e një visi. Për Dejan Jović, Jugoslavija - država koja je odumrla Translated by (Macedonian to Albanian): Lindita Ahmeti Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 2, No. 2 (Winter 2003) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 151-157 Page Count: 7 Citation (Macedonian): Ирена Стефоска, „И-сторија за еден крај. Кон Dejan Jović, Jugoslavija - država koja je odumrla“, Идентитети: списание за политика, род и култура, т. 2, бр. 2 (зима 2003): 151-157. Citation (Albanian): Irena Stefoska, „Rrëfimi për historinë e një visi. Për Dejan Jović, Jugoslavija - država koja je odumrla“, përkthim nga Maqedonishtja Lindita Ahmeti, Identities: Journal for Politics, Gender and Culture, Vol. 2, No. 2 (Winter 2003): 151-157.